Kemampuan Pemecahan Masalah Dan Disposisi Matematis Pada Materi Kubus Dan Balok Ditinjau Dari Kemampuan Matematika - ali suwito, uswatun hasanah; Handayani, Aprilia Dwi; Yohanie, Dian Devita; uswatun hasanah (Efektor, 2021)
This research is motivated by the importance of problem-solving abilities and mathematical dispositions on cube and block material in terms of mathematical abilities. Where the objectives of learning mathematics contain cognitive aspects seen from problem-solving abilities and affective aspects which can be seen from mathematical dispositions. The purpose of this study was to describe problem solving abilities and mathematical dispositions, as well as the relationship between the two in the cube and block material in terms of mathematical abilities. This research was conducted at SMP Pawyatan Daha 2 Kediri City with the research subjects of class IX. The approach used is a qualitative approach. Data were collected by giving test questions of problem-solving abilities, giving mathematical disposition questionnaires, and interviews based on the results of test questions by each subject. The conclusions of the results of this study are (1) The problem-solving ability of students is generally in quite good criteria (2 Students' mathematical disposition is generally in good criteria, and (3) There is no significant relationship between problem-solving abilities and mathematical dispositions.